OWE-28 Post-imaging colorectal cancer in the english national health service bowel cancer screening programme. (June 2019) - Derbyshire, Edmund; Plumb, Andrew; Nickerson, Claire; Moores, Billie; Wright, Suzanne; Morris, Eva; Valori, Roland; Rutter, Matt
Abstract : Introduction: Computed tomography colonography (CTC) is the gold standard radiological investigation for colorectal cancer screening. The Post-Imaging Colorectal Cancer (PICRC) rate (i.e. colorectal cancers that develop after a negative CTC) is a key quality indicator of CTC; however, PICRC rates have not been previously reported in a national programme. The Word Endoscopy Organisation has, through a consensus process, agreed a standard methodology for calculating PICRC rates to enable international benchmarking (1). This rate (which the WEO terms PICRC-3y) is calculated by dividing the PICRCs detected 6 months to 3 years after a negative CTC (false negatives) by the sum of the true positives (defined by CTCs with a cancer diagnosis within 6 months) and false negatives (PICRCs). This study aimed to determine the rate of PICRC-3y in the English National Health Service (NHS) Bowel Cancer Screening Programme (BCSP). Methods: Data from each Bowel Cancer Screening Programme (BCSP) CTC is entered into a national database, the Bowel Cancer Screening System (BCSS). All colorectal adenocarcinomas, within and outside the BCSP, are validated and registered by the National Cancer Registration and Analysis Service (NCRAS). This retrospective observational study interrogated these databases to identify BCSP true positive and false negative CTCs. CTCs were included regardless of whether they were preceded or followed by a colonoscopy within a screening episode. Results: Of the 8 PICRCs, 3 were detected at subsequent BCSP procedures, one at 1 year surveillance, and 2 following re-invitation for screening at 2 years. Five were detected outside the BCSP. Conclusions: The PICRC–3y in the BCSP is higher than the rate in the published literature (4.4%)(2) and the corresponding rate for Post Colonoscopy Colorectal Cancer (PCCRC) over the same period (2.5%). CTC is commonly reserved for patients who are either deemed unsuitable for colonoscopy, or in whom colonoscopy has failed, meaning that there are likely to be substantial differences between the populations undergoing each examination. Because CTC and colonoscopy are performed in different populations, those having CTC more likely to be frailer with greater co–morbidity, the higher rate of PICRC when compared to PCCRC has to be interpreted with caution and may relate to the difficulty of investigating such patients, who may not be fit enough for, or refuse an intervention even if a lesion is found. References: Beintaris I, et al. United European Gastroenterology Journal Vol 5 Issue 5_Suppl PO436 Obaro AE, et al. Lancet Gastroenterol Hepatol3(5) 32–36